EFEKTIVITAS PROGRAM KELUARGA HARAPAN DI KECAMATAN GAYAMSARI KOTA SEMARANG - Rafika Yolanita; Tri Yuniningsih (Journal of Public Policy and Management Review, 2020)
The government has established a prospect family program as one of the poor handling efforts. However, the implementation of prospect family program in Gayamsari Sub-district of Semarang is still not able to run effectively because it is still found the area that has many receivers outside the household is very poor, high graduations capable, and high Percentage of funds that have not been extended. The purpose of this research is to analyse the effectiveness of the prospect family program in Gayamsari Sub-district of Semarang. The method used is a qualitative-descriptive approach with data collection techniques through observation, interviews, and documentation. This study uses the theories of Makmur, Campbell, and Nugroho about the criteria of program effectiveness, that is the accuracy of the goals, the accuracy of the objectives, satisfaction with the program, and the accuracy of the implementer. The results of this study indicate that the effectiveness of the family expectation program in terms of targeting accuracy, goal accuracy, and program satisfaction has not been effective, because there are still obstacles in its implementation, while the accuracy of the implementers has been able to run well. This is influenced by inhibiting factors such as the absence of an MoU, the emergence of social jealousy, KPM behavior that does not carry out its obligations, excessive co-worker workload, and poor quality system. The recommendation is to improve the socialization of the program, create a memorandum of understanding that governs cooperation between stakeholders, increased employment of KPM obligations, the addition of escort personnel, and improve the system PKH reports. Keywords : effectiveness, prospect family program, pov